Virtual professional development on conflict management for school leaders - Irby, Beverly J.; Pashmforoosh, Roya; Druery, Donna M.; Lara-Alecio, Rafael; Tong, Fuhui; Etchells, Matthew J.; Algert, Nancy T. (Frontiers in Education, 2022)
From 2017 until 2020, we held face-to-face professional development focused on enhancing instructional leadership for underserved schools at the campus level. We quickly determined in March 2020, based on the predicted situation of COVID-19, that we needed to change that venue to virtual professional development (VPD). The study was grounded in the theoretical base of adult learning theory and transformational learning since we were working with school leaders. The researchers used a mixed methods research design with a survey to examine to what extent school leaders perceived their engagement in a synchronous VPD webinar with facilitators increased their knowledge on the topic of conflict management. The findings showed that the participants perceived targeted VPD to have significantly increased their knowledge on conflict management. Additionally, the participating school leaders indicated a shift in their attitudes from negative to positive perceptions regarding conflict. The findings suggest that structured VPD for school leaders has the potential to advance school leaders’ knowledge on conflict management.